(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To analyze some factors related to the knowledge and practice of rabies prevention among people coming to get rabies vaccines at the Hau Giang provincial Center for Disease Control in 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 370 people coming to get rabies vaccines at the Hau Giang provincial Center for Disease Control in 2025. Results: Statistically significant associations were found (p < 0.05). Notably, education level and access to official information sources were two factors strongly related to correct knowledge. People with a high education level were 4.2 times more likely to have correct knowledge than the junior high school group, and those who accessed official information sources were 1.8 times more likely. Correct knowledge was a prerequisite for correct practice, as those with correct knowledge were 4.2 times more likely to have correct practice than the group with incorrect knowledge. Conclusion: Correct knowledge increases the likelihood of correct practice by 4.2 times, confirming that knowledge is the strongest prerequisite for behavior change. This knowledge, in turn is strongly influenced by education level and access to official information sources. This strongly reinforces the recommendation that public health interventions must prioritize improving knowledge, as this is the key to changing community health protection behaviors.